Quantitative Analysis of Silicon Tetrachloride, Carbon Disulfide, and Dichloroethane Concentration by Raman Spectroscopy. (16th February 2023) - Xiang, Xiaoyan; Shao, Yufeng; Wei, Yanfang; Xia, Wentang; Yuan, Xiaoli
Abstract : Quantitative analysis of silicon tetrachloride, carbon disulfide, and dichloroethane concentrations to obtain vapor-liquid equilibrium data of the SiCl4 -CS2 and SiCl4 -C2 H4 Cl2 binary systems was established by Raman spectroscopy. The cheap glass sampling pipe was used as a carrier for Raman spectroscopy measurements. The Raman peak height of the internal standard was used to remove interference factors such as sampling pipe diameter, temperature, laser power, and other effects from the instrument. The peak height ratio between the Raman characteristic peak of the analyte and that of the internal standard was proportional to the analyte concentration. During the measuring process of vapor-liquid equilibrium data for the SiCl4 -C2 H4 Cl2 binary system, the linear equation of y = 0.0068 + 0.75 x with R 2 of 0.9939 was used for the determination of SiCl4 concentration at the 422 cm −1 band. The linear equation of y = 0.0019 + 0.2266 x with R 2 of 0.9966 was used for the determination of C2 H4 Cl2 concentration at the 754 cm −1 band. For the SiCl4 -CS2 binary system, the linear equation of y = 0.0494 + 4.7535 x with R 2 of 0.9962 was used for the determination of SiCl4 concentration at the 422 cm −1 band. The linear equation of y = 0.8139 + 8.7366 x with R 2 of 0.9973 was used for the determination of CS2 concentration at the 654 cm −1 band. The concentration of standard samples calculated by these standard curves was compared with the actual value to verify the accuracy of this method. The reproducibility is good when determining silicon tetrachloride and dichloroethane concentrations for the SiCl4 -C2 H4 Cl2 binary system, with RSEP values of 2.81% and 2.17%, respectively. Meanwhile, the RSEP values are 3.55% and 4.16%, respectively, when determining silicon tetrachloride and carbon disulfide concentrations for the SiCl4 -CS2 binary system.